THE IDEOLOGY OF „GREATER KOSOVO“ IN THE VISION OF ALBANIAN NARCO-TERRORIST CLANS - Mijalković, Saša; Popović Mančević, Marija Lj. (NBP. Nauka, bezbednosti, policija, 2020)
The paper reviews the evolution of the ideology and the way of creating the Albanian state in the Balkans, from the moment when it did not exist at all (during the Ottoman Empire) until today, when Albanians live in an internationally recognized state (Republic of Albania) and in one self-proclaimed state (the so-called "Republic of Kosovo"). In that regard, this paper is based on two theses. According to the first, the focus of the original so-called state-building ideology about the need for all Albanians to live in one state, "Greater Albania", today is radically changed and diametrically opposed: "Kosovo Albanians" now do not want to join the Republic of Albania, but want an independent state - the so-called "Greater Kosovo", which would include parts of the territories of central Serbia, Montenegro, Northern Macedonia and Greece where Albanians live. The reason for the essential change of ideology is that the drug bosses of Albanian criminal clans that control the territory of Kosmet, and who were previously commanders of Albanian terrorist organizations, want their own "drug state", in which they would control all social flows and enjoy immunity from criminal prosecution. The second thesis on which this paper is based is that the attack on the Albanian mafia is at the same time a blow to the so-called quasi-statehood of the so-called Republic of Kosovo, ie on the levers of financial power, which is the backing for political power and international support for the so-called Republic of Kosovo.